"Zelena ekonomija" i "zeleno preduzetništvo" u kontekstu održivog rasta i razvoja u Crnoj Gori / The "Green Economy" and the "Green enterpreneurship" in the Context of Sustainable Economic Growth and Development in Montenegro - Gardašević, Ana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
In this paper, thanks to the analysis of basic macroeconomic indicators, there will be provided an overview of the Montenegrin economy which will emphasize structural defects in terms of the global economic and financial crisis. Unsustainable export structure, lack of competitiveness of domestic production, high public debt and unemployment, are just some of the indicators that question the sustainability of the current growth model of the Montenegrin economy. The growth model that would focus on the green economy and the green entrepreneurship could be a strong growth driver in the future and an important direction of sustainable development of the Montenegrin economy.